Measuring Effectiveness of Project Communication Channels in Affected Communities in Nepal - Ghimire, Prabhakar (Curriculum Development Journal, 2021)
This study is identifying the most appropriate communication medium to communicate with local people by Arun-3 Hydropower Project (AHPP) especially focusing on the project construction phase. Since, the study is focused on the construction period when chances of misunderstanding, miscommunication, and other conflicts between project-affected people and the project, will be high due to higher incidences of social and environmental issues. This study was completed by applying mix method of research where quantitative research was conducted through a survey among local people of Makalu Rural Municipality (MRM) of Sankhuwasabha and a case interview was done with the chairman of the same Rural Municipality. The study has revealed that local radios and public meetings are the most recommended mediums that participants expected to support the project in properly disseminating project-related information to local people. This article suggests that AHPP should disseminate information about project activities mainly through local radios and public meetings. This study also concludes that the project developer is not providing sufficient information about project activities to local people, which is also a source of misunderstanding between the two sides.